Analysis of Indoor Residential Environment Satisfaction among Social Housing Households in Seoul - Sang-Hyun Chung; Jun Ha Kim (Buildings, 2023)
Social housing in Seoul has been provided since 2015 via collaboration between the city and the private sector to address the increasing housing burden for single-person households and the younger generation. Despite the eight years since the implementation of this initiative, there remains a lack of research regarding the satisfaction of residents with respect to indoor social housing environments. The aim of this study is two-fold: (1) to explore household characteristics, such as floor area and living room, bathroom, and kitchen issues; and (2) to examine the factors that affect indoor residential environment satisfaction. In May and June of 2022, 57 households from 22 social housing projects participated in the survey, and data were analyzed using frequency and descriptive methods. The results indicated that the interior layout of the house affected and influenced residential satisfaction. This was followed by accessibility to major facilities, interactions with the community, accessibility to transportation, and facility maintenance. The implications of these findings were discussed.